2021
DOI: 10.3390/foods10020287
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Aflatoxin- and Fumonisin-Producing Fungi Associated with Cereal Crops Grown in Zimbabwe and Their Associated Risks in a Climate Change Scenario

Abstract: In most sub-Saharan African countries, staple cereal grains harbor many fungi and some produce mycotoxins that negatively impact health and trade. Maize and three small grain cereals (sorghum, pearl millet, and finger millet) produced by smallholder farmers in Zimbabwe during 2016 and 2017 were examined for fungal community structure, and total aflatoxin (AF) and fumonisin (FM) content. A total of 800 maize and 180 small grain samples were collected at harvest and during storage from four agroecological zones.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 62 publications
(91 reference statements)
1
32
0
1
Order By: Relevance
“…Although changing dietary habits may be difficult (food scarcity, high food prices, resilience to change diet type), farmers and value chain actors are encouraged to consume more foods prepared with non-susceptible crops. In both Uganda and Zimbabwe, millets were found to be less susceptible to aflatoxin and other mycotoxins than the most preferred maize and sorghum and the authors recommended greater consumption of millets (Bandyopadhyay et al, 2007;Wokorach et al, 2020;Akello et al, 2021).…”
Section: Integrated Aflatoxin Managementmentioning
confidence: 99%
“…Although changing dietary habits may be difficult (food scarcity, high food prices, resilience to change diet type), farmers and value chain actors are encouraged to consume more foods prepared with non-susceptible crops. In both Uganda and Zimbabwe, millets were found to be less susceptible to aflatoxin and other mycotoxins than the most preferred maize and sorghum and the authors recommended greater consumption of millets (Bandyopadhyay et al, 2007;Wokorach et al, 2020;Akello et al, 2021).…”
Section: Integrated Aflatoxin Managementmentioning
confidence: 99%
“…18,26 It was asserted that the manner of field collection and storage condition of certain grains accounted for reduced ZEA contamination of certain farm produce. [37][38][39][40] The Seasonal timing of collection of produce could also contribute to the trend observed in the result, since the samples were obtained during the very dry weather of December. Investigations revealed that climate and weather are also significant determinants of cereals and legumes predisposition to mycotoxin contamination.…”
Section: Resultsmentioning
confidence: 96%
“…Indeed, under the most probable scenario of warming (e.g., +2°C), aflatoxin B 1 was predicted to become a food safety issue in maize in Europe within 100 years (Battilani et al, 2016). Improperly stored commodities may see increases in mycotoxins (Paterson and Lima, 2010;Magan et al, 2011;Medina et al, 2015;Akello et al, 2021). Increased weather extremes, including flooding or drought, greatly affects water quality in a region and can result in increased pathogen transfer in post-harvest handling (Atanda et al, 2011).…”
Section: Climate Change-induced Alterations In Postharvest Quality Of...mentioning
confidence: 99%
“…More recently, Medina et al (2017) found Aspergillus flavus was likely to be unaffected by climate change factors (elevated CO 2 , temperature, moisture), but that there was a significant stimulation in the production of its mycotoxin, aflatoxin B 1 in vitro and in vivo in corn. However, cereal grains grown in drier and hotter areas of Zimbabwe had higher A. flavus contamination, while there was more fumonisin content in wetter years (Akello et al, 2021). In Malawi, warmer and drier conditions from climate change are predicted to make pre-harvest conditions more favorable to aflatoxin B 1 contamination, with contamination risk increasing at more northern regions (Warnatsch et al, 2020).…”
Section: Climate Change-induced Alterations In Postharvest Quality Of...mentioning
confidence: 99%